Digital Gene Expression Analysis of Huanglongbing Affected Mandarins (Citrus reticulata Blanco) In Response to Thermotherapy - Ruixuan Pan; Yanling Chen; Xiaoling Deng; Meirong Xu (Horticultural Plant Journal, 2021)
Huanglongbing (HLB), which is mainly associated with “Candidatus Liberibacter asiaticus” (CLas), is currently threatening citrus production around the world. This destructive century-old disease results in callose deposition in phloem plasmodesmata and starch overaccumulation in leaf chloroplasts. Heat treatment with high humidity has proven to be effective in eliminating the CLas titers in potted citrus trees. This study explored the curative mechanisms and impact of heat treatment (from 32 to 48 °C with 75% ± 5% relative humidity, 14 h in light and 10 h in dark for four days) on mandarin trees (Citrus reticulata Blanco) that were severely infected by CLas using Solexa/Illumina's digital gene expression (DGE) profiling. A total of 838 differentially expressed genes (DEGs) were identified, of which 510 were downregulated. Protein-protein interaction analysis of the DEGs indicated that the thermotherapy of HLB trees downregulated the circadian clock related genes in chloroplasts and upregulated the RNA-editing process in the mitochondria, characterized by 141 genes encoding pentatricopeptide repeat-containing proteins (PPR) being all upregulated. Furthermore, the expression of phenylpropanoid and flavonoid biosynthesis genes, and auxin-induced genes were suppressed. The defense response pathway of the thermotherapy treated diseased trees was apparently disrupted, as indicated by the downregulation of LRR receptor-like serine/threonine-protein kinase FLS2 gene. This study improves our understanding of the curative mechanisms of heat treatment on HLB trees and CLas biological regulation. Importantly, this provides new insights on the involvement of RNA modification by PPR genes and changes in the circadian clock after the heat stress treatment of CLas-infected citrus.